Język mniejszości jako czynnik zachowania tożsamości grupowej na przykładzie polskich staroobrzędowców w regionie suwalsko-augustowskim - Głuszkowski, Michał (Acta Polono-Ruthenica, 2008)
In this text the connections between the group identity and its language are described. The identity is here understood as self-determination of group members, their common history, religion, language, sense of integrity and tradition belonging to all the individuals in the group. The selfconsciousof bilingual group’s members can affect their language behaviour and the level of competencein each of their languages. The language itself, can be a kind of marker emphasising the differences between the group members and the outer world. Depending on the situation and conditions, this fact may be underlined or disguised. The language can be a strong factor supporting the group identity. On the other hand, the sense of bond with tradition and minority’s values, influence the language structure and act a role of an important non-structural factor, which can strengthen or reduce total amount of language interference. Thus, the influence and connections between the group’s identity and its language, are mutual.